Analisis Quality of Service (QoS) pada jaringan internet Fakultas Ilmu Komputer Universitas Sjakhyakirti - Ade Sukma Wati; Putri Maharani; Bakhtiar K3 (Rey Media Grafika, 2025)
The internet network is very useful for adding insight and knowledge, connecting communication between one individual and another. According to data from speedtest.net for the month of Mei 2023, it is known that the average internet network speed in Indonesia for cellular data is 22.08 Mbps. Based on the speedtest test, the speed of using the internet network for download is 45.40 Mbps and the upload speed is 16.14 Mbps. A very precise internet network, requires a Quality of Service (QoS) service. This analysis is used to determine the value or quality level of the available internet network services.